Does the use of slow release prostaglandin delivery systems increase the risk of sepsis in patients with preterm premature rupture of membranes?. (18th April 2012) - Lahiri, S; Ismail, A; Sharma, S
Abstract : Most Obstetric Units in England and Wales are increasingly using slow release prostaglandin delivery systems as the first line for induction of labour. For women with premature rupture of membranes at term there is no difference in the outcome between the use of prostaglandins and intravenous syntocinon. This does not apply to women who have had preterm prelabour rupture of membranes (PPROM) where cervical ripening has not occurred. PPROM complicates 2% of pregnancies. The recommendation is to offer induction of labour after 34 completed weeks of gestation. We present three patients who had PPROM, managed conservatively and then went on to have induction of labour with slow release prostaglandin delivery systems. All three women had normal vaginal deliveries and the infants were found to have non streptococcal septicemia and needed admission to the Neonatal Unit. Patient with prolonged rupture of membranes are at a higher risk of chorioamnionitis with upto one third of the pregnancies having positive amniotic fluid cultures. Infants born with sepsis have a mortality four times than those without. The placement of a slow release pessary in the vagina for twenty four hours for induction of labour may increase the risk of clinical chorioamnionitis by acting as a foreign body. More prospective studies are needed to ascertain the risk in this particular group of patients.